2016
DOI: 10.1016/j.bpj.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Pericellular Brush and Mechanics of Guinea Pig Fibroblast Cells Studied with AFM

Abstract: The atomic force microscopy (AFM) indentation method combined with the brush model can be used to separate the mechanical response of the cell body from deformation of the pericellular layer surrounding biological cells. Although self-consistency of the brush model to derive the elastic modulus of the cell body has been demonstrated, the model ability to characterize the pericellular layer has not been explicitly verified. Here we demonstrate it by using enzymatic removal of hyaluronic content of the pericellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…Other models could be used for this task. One fairly new and accurate is the "Brush Model" developed by Sokolov et al [40][41][42], which can be useful to isolate the mechanical response of the cell from deformation of the pericellular layer surrounding the cell itself. The model used in the present study does not consider the brush but was chosen as (i) it is the most commonly used model, (ii) the same protocol/methodology has been used for all cells and indentations.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Other models could be used for this task. One fairly new and accurate is the "Brush Model" developed by Sokolov et al [40][41][42], which can be useful to isolate the mechanical response of the cell from deformation of the pericellular layer surrounding the cell itself. The model used in the present study does not consider the brush but was chosen as (i) it is the most commonly used model, (ii) the same protocol/methodology has been used for all cells and indentations.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Five micrometer silica AFM probes were used in this study. The probes were prepared by utilizing tipless AFM cantilevers (Bruker, Inc., Santa Barbara, CA, a nominal spring constant of 0.06 N m −1 ; the exact spring constant was defined using thermal tuning method before gluing the silica probe) as described, e.g., in the study by Dokukin et al [ 32 ] Force maps (16 × 16 and 32 × 32 pixels) with a vertical ramping size of 5 μm were recorded for each cell and cell's cluster correspondingly. Vertical speed in all experiments was set to 5 μm s −1 , allowed to record one pixel within 1.5 s. For an example of 16 × 16 pixels, the time of acquisition of such a map will be 16 × 16 s, which is a bit more than 6 min; acquisition of 32 × 32 pixel image will require 26 min.…”
Section: Methodsmentioning
confidence: 99%
“…This model was suggested in the study by Sokolov et al, [ 30 ] and later developed in previous studies. [ 9,31,32 ] As was shown, considering the pericellular layer and the use of a large colloidal probe are essential for self‐consistency of the Hertz model, which is used to extract the effective Young's modulus of the cell body (note that the Hertz model is used because there is no adhesion between the AFM probe and cell surface measured in liquids). This model is described in detail in the references mentioned earlier and recently overviewed.…”
Section: Afm In Studying Cellsmentioning
confidence: 99%
“…Nikkhah et al (2011) reported that nonmalignant breast epithelial cells had significant higher Young's moduli than their malignant counterparts. Dokukin et al (2016) reported that the force signature of the pericellular brush layer of Guinea pig fibroblast cells was significantly changed after a treatment with hyaluronidase. Kasas et al (2013) investigated the nanomechanical properties (Young's modulus, deformability and adhesion) of biological samples (mammalian cells, plant cells, yeast cells, bacteria and viruses).…”
mentioning
confidence: 99%